AN INVESTIGATION INTO THE PSYCHOLOGICAL CHARACTERISTICS OF HIGH-RISK GAMING DISORDER INDIVIDUALS WITH VARIED TIME PERSPECTIVES - Shan, Haidi (LIFE: International Journal of Health and Life-Sciences, 2024)
Previous research has demonstrated that past-negative, present-hedonistic, and present-fatalistic time perspectives are risk factors for addiction, while a future time perspective serves as a protective factor. However, the influence of time perspectives on gaming disorder and the psychological differences among individuals with different time perspectives remain unclear. A total of 210 high-risk gaming disorder individuals and 121 low-risk controls were recruited from a university student population. Participants completed the Zimbardo Time Perspective Inventory (ZTPI), Barratt Impulsiveness Scale (BIS-11), Motives for Online Gaming Questionnaire (MGQ), and Monetary Choice Questionnaire (MCQ). Cluster analysis was performed using the five subscales of ZTPI (past-positive, past-negative, present-hedonistic, present-fatalistic, and future) as clustering indicators to group the high-risk gaming disorder individuals. Network analysis was employed to compare the differences in network structure and connection strength among different cluster groups. Based on the cluster analysis, the high-risk gaming disorder individuals were divided into two groups. Compared to the control group, Cluster 1 showed higher scores in present-hedonistic dimension, and lower scores in the past-positive and future dimensions. Cluster 2 exhibited higher scores in past-negative, past-positive, present-hedonistic, and present-fatalistic dimensions. Cluster 1 scored significantly lower than Cluster 2 in all five dimensions. In terms of psychological differences, Cluster 2 showed significantly higher scores in gaming's social motives, immersion motives, and gaming-induced improper behavior compared to Cluster 1. Network comparison analysis revealed that Cluster 1 had significantly higher network structure strength than Cluster 2, with significantly stronger connections between past-positive and future dimensions. Distinct differences exist among high-risk gaming disorder individuals with different time perspectives regarding immersion in gaming, social motives, and gaming-induced improper behavior. Interventions and directions for different categories of high-risk gaming disorder individuals should be more targeted, particularly focusing on reinforcing positive past experiences and empowering future orientations.